Investigating the Impact of Indemnity Waivers on the Length of Stay of Cats at an Australian Shelter - Jessica Pockett (Animals, 2019)
Due to resource limitations, animal shelters in Australia historically have focused on rehoming animals considered ‘highly adoptable’. Increasingly, animal shelters in Australia are rehoming animals with pre-existing medical and/or behavioural issues. These animals are often rehomed with an ‘indemnity waiver’ to transfer the responsibility of ongoing financial costs associated with these conditions from the shelter to the new owner. However, it is unknown what effect these indemnity waivers have on the length of stay (LOS) of animals prior to adoption. The current study used data collected from the Royal Society for the Prevention of Cruelty to Animals (RSPCA) Weston shelter located in the Australian Capital Territory (ACT), Australia in 2017 to investigate the effect of indemnity waivers on the LOS of cats. A restricted maximum likelihood model (REML) was used to determine the effect of breed, age, coat colour, presence of a waiver, waiver type (categorised into seven groups) and waiver number (no waiver, single waiver or multiple waivers) on LOS. In the final multivariate model, age, breed and waiver number were found to influence LOS. Young cats, purebred cats and cats adopted without a waiver were adopted fastest. This study is the first to report the effect of indemnity waivers on the adoptability of cats from shelters.